Interconnection of LANs through ISDN. - Liu, Zhengyu. (University of Ottawa (Canada), 1991)
Network interconnection (internetworking) is an important issue in the area of computer communication. One of the purposes of internetworking is to allow communication to go beyond a single local area network (LAN). In this thesis, networks interconnection is studied. An internetworking device - (gate-way) is proposed to provide the capability of internetwork data transmission between LANs through an ISDN (Integrated Service Digital Network). This gateway is an application layer program which interfaces with the NetBIOS (Network Input Output System), a widely implemented interface between application programs and LANs in the IBM personal computer world. The NetBIOS interface is provided in both LAN and ISDN environments in a connection-oriented mode. A facility for file transfer and information exchange among LANs through ISDN is developed in such a way that it neither affects the existing network hardware and software available in both LANs and ISDN nor changes the mechanism of communication within a LAN. In particular, the emphasis is given to the specification, design and implementation of the gateway. In our model, the gateway is specified with a finite state machine. Based on the model, the gateway is designed by considering the issues of naming, name assigning, buffering, session handling, multi-session managing and error processing. A prototype of the gateway is implemented on a PC/XT computer with a LAN adapter, an ISDN adapter and the gateway program coded in "C". Performance benchmarks are conducted in terms of two factors: Message size and background traffic. These factors may affect the performance of internetwork data transmission. Finally, test results on different network conditions are given.
Keywords: Engineering, Electronics and Electrical.